Internet-based exercise and physical activity promotion for persons with multiple sclerosis: a randomized controlled trial - Hartung, Verena; Tallner, Alexander; Flachenecker, Peter; Mäurer, Mathias; Streber, René; Wanner, Philipp; Rashid, Asarnusch; Shammas, Layal; Hois, Gottfried; Dettmers, Christian; Roick, Holger; Stefanou, Alexander; et al. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background: We evaluated the effects of a 12-week internet-based exercise and physical activity promotion program for persons with multiple sclerosis. Methods: We performed a multicenter, randomized, waitlist-controlled study. The intervention group (IG) received the 12-week program, followed by 12 weeks with usual care. The control group (CG) received usual care only. The main components of the 12-week program were: (1) a tailored home-based exercise prescription, (2) e-learning resources, (3) telephone and video meetings with an exercise therapist, (4) the provision of a consumer-based PA monitor. Measurements were taken at baseline, postintervention, and after 24 weeks. The primary outcome was device-measured steps/day. Other outcomes were device-measured moderate-to-vigorous physical activity, subjectively measured leisure-time and transportation physical activity and sport/exercise, physical activity-related health competence, walking ability, quality of life, fatigue, depression, and PA-related self-concordance. We compared changes from baseline to postintervention between groups and analyzed changes in the IG during the follow-up. Results: Analysis of 56 persons with multiple sclerosis (IG: n = 29, CG: n = 27, age: 45.6 ± 10.9) revealed no significant intervention effect on steps/day. However, significant improvements were observed in moderate-to-vigorous physical activity, sport/exercise, control competence, fatigue, and quality of life (physical). During the follow-up, sport/exercise and quality of life decreased significantly. Leisure-time and transportation physical activity increased significantly. Conclusions: Our study provides first evidence that the developed program can increase control competence, aspects of physical activity and health in persons with multiple sclerosis. A trial with a larger sample is recommended to confirm our results and examine intervention mechanisms. Trial registration: Registry: Clinicaltrials.gov; registration number: NCT04367389; date of registration: 2020-04-21 (retrospectively registered).
CRIS-Team Scopus Importer:2025-05-02
Keywords: Behavior change; Exercise; Internet-based intervention; Multiple sclerosis; Physical activity; Physical activity-related health competence